O losie, starości i przemijaniu = The synopsis of the article "Of fate, old age and passing of life" - Frąckowiak, Tadeusz (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The article confronts the problem stated in the title, which incorporates ethnology of education, social pedagogy and human philosophy. Each of the three theoretical categories (fate, old age, passing of life) relates to the problem of the sense of life. The broad social and existential context of the maxim "all is vanity" defines contemporary state of culture and civilisation and does not relinquish the search for definitions of life and humanity, attempting to prove that education is conceivable of supporting the struggle against fate, old age and passing of life as well as of assisting with choosing the right life-strategies through training how to make an effort. Each human being needs to posses the conscious perception of his kind and species to provide others with the chance for life and to acknowledge its great value.
Keywords: edukacja; pedagogika społeczna; filozofia człowieka